2020
DOI: 10.1177/0022022120939655
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Self-Construal and in Depressive Symptoms: Predictors of Cross-National Variation

Abstract: Sex differences in aspects of independent versus interdependent self-construal and depressive symptoms were surveyed among 5,320 students from 24 nations. Men were found to perceive themselves as more self-contained whereas women perceived themselves as more connected to others. No significant sex differences were found on two further dimensions of self-construal, or on a measure of depressive symptoms. Multilevel modeling was used to test the ability of a series of predictors derived from a social id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…Response scales for these items were the same as those used for the self-construal items. Smith et al (2020) confirmed the intended factor structure of these items through multilevel confirmatory factor analysis, using MPlus Version 8 (Muthén & Muthén, 1998. They specified two covarying factors at both participant and sample levels, one representing a factor indicated by the six discomfort items, and one indicated by the three avoidance items.…”
Section: Methodsmentioning
confidence: 58%
See 4 more Smart Citations
“…Response scales for these items were the same as those used for the self-construal items. Smith et al (2020) confirmed the intended factor structure of these items through multilevel confirmatory factor analysis, using MPlus Version 8 (Muthén & Muthén, 1998. They specified two covarying factors at both participant and sample levels, one representing a factor indicated by the six discomfort items, and one indicated by the three avoidance items.…”
Section: Methodsmentioning
confidence: 58%
“…Smith et al (2020) report analyses of this data. Following Kashima et al (1995), individual variations in response style were first discounted through within-subject standardization.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations